2022
DOI: 10.3390/pharmaceutics14071345
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Platforms for Treating Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) is the first leading cause of death globally. Nitric oxide (NO) is an important signaling molecule that mediates diverse processes in the cardiovascular system, thereby providing a fundamental basis for NO-based therapy of CVD. At present, numerous prodrugs have been developed to release NO in vivo. However, the clinical application of these prodrugs still faces many problems, including the low payloads, burst release, and non-controlled delivery. To address these, various biomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 151 publications
0
8
0
Order By: Relevance
“…Various types of NO donors, like glyceryl trinitrate (GTN), sodium nitroprusside (SNP), diethylamine diazeniumdiolate (DEA/NO), and RSNOs, RIG200 are currently being explored as possible mechanisms to achieve a sustained release of NO in cardiovascular systems. [ 233 ] Flierl et al. demonstrated low adhesion of activated platelets to fibrinogen in the presence of pentaerythritol tetranitrate (PETN; NO donor) by 50% compared to the control (untreated fibrinogen samples).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of NO donors, like glyceryl trinitrate (GTN), sodium nitroprusside (SNP), diethylamine diazeniumdiolate (DEA/NO), and RSNOs, RIG200 are currently being explored as possible mechanisms to achieve a sustained release of NO in cardiovascular systems. [ 233 ] Flierl et al. demonstrated low adhesion of activated platelets to fibrinogen in the presence of pentaerythritol tetranitrate (PETN; NO donor) by 50% compared to the control (untreated fibrinogen samples).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…So, the effect of different NO donors in the presence of these scavengers needs to be properly exploited to better understand the aggregation effect of the activated platelets. [ 233a ] Sogo et al reported not only the platelet inhibitory effect of each NO donor (e.g., GTN, SNP, GSNO, DEA/NO, and RIG200) but also the effect of endogenous NO scavengers on the attachment of activated platelets to a collagen treated surface. Fe(II)Hb and ODQ inhibited the effect of the NO donors.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Decreased NO synthesis, release, and/or activity in ECs have been associated with the development of CVD. 45 NO, a highly reactive and gas diffusible free radical with potent vasodilatory, anti-inflammatory, and antioxidant properties, plays key roles in regulating vascular tone, angiogenesis, inflammatory cell adhesion, and platelet aggregation. 46 The biosynthesis of NO in ECs is catalyzed by endothelial nitric oxide synthase (eNOS).…”
Section: Decreased No Productionmentioning
confidence: 99%
“…This leads to vasoconstriction, reduced blood flow, and elevated blood pressure, all of which contribute to the development of cardiovascular diseases 34 . Several drugs target the NO pathway for treating hypertension CVDs, 39 including ACE inhibitors, angiotensin receptor blockers, and organic nitrate drugs. These drugs either increase or enhance NO production, leading to vasodilation, reduced blood pressure, and improved cardiovascular function 40 .…”
Section: Hypertension and Cardiovascular Diseasesmentioning
confidence: 99%